ANALISIS KINERJA INDUSTRI KETAK, TENUN, DAN GERABAH DI KABUPATEN LOMBOK TENGAH - hamid, hamid (Jurnal Sains dan Teknologi Indonesia, 2008)
Industry sector especially small industry sub-sector is one of dominated activities in rural area of Lombok Tengah Regency. From these small industries, industry of ketak, tenun and gerabah have big role and contribution for the economic development in this area. However, recently they are still facing constraints or obstacles mainly in order to improve and develop their production factors such as labor, capital, natural resources/raw material, technology, and marketing. It is needed to make constructive efforts for improving the production factors performance of these three kinds of small industries in order to improve the product competitiveness and the welfare of the industrial agents in Lombok Tengah Regency.